Resilient Critical Infrastructure management with a service oriented architecture: a test case using Airport Collaborative Decision Making - Hall-May, Martin; Surridge, Mike; Nossal-Tüyeni, Roman (Zielona Góra: Uniwersytet Zielonogórski)
The SERSCIS approach aims to support the use of interconnected systems of services in Critical Infrastructure (CI) applications. The problem of system interconnectedness is aptly demonstrated by "Airport Collaborative Decision Making" (A-CDM). Failure or underperformance of any of the interlinked ICT systems may compromise the ability of airports to plan their use of resources to sustain high levels of air traffic, or to provide accurate aircraft movement forecasts to the wider European air traffic management systems.
Keywords: resilience; QoS; SOA; critical infrastructure; SLAM